Analysis of the Application of Project-Based Learning on Children's Independence: Case Study at the American Academy Casablanca Morocco - Nurhusna Kamil; Haseena Sultan (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2022)
Independence is one of the life skills that individuals must possess, especially in early childhood. This ability must be introduced and instilled earlier in children. Independence has been taught by parents from home and even continues when children enter the world of education with the help of teachers. Parents will feel many impacts when instilling independence is implemented earlier, one of which is the absence of dependence on children to complete their tasks. The research method used is qualitative with a case study approach. This research aims to use a case study approach to see the application of project-based learning for children's independence at the American Academy Casablanca in Morocco. The target research was aimed at the American Academy Casablanca school in Morocco with a large population of 10 children, all used as research samples with two teachers. Data sources were obtained from secondary data and primary data. The secondary data researchers obtained from one of the teachers who taught at the institution, while the primary data was obtained from books and articles related to the research. Data collection techniques include interviews and results of documentation. While data analysis starts from the stages of data reduction, data presentation, drawing conclusions, and verification as needed. The research found that there is a link between the application of this learning model to children's independence during the media selection process and activities during learning. The findings from this study show that there is a significant effect of the application of project-based learning on independence in early childhood so that it can be used as an alternative in applying this ability as well as other abilities according to the desired educational goals.